Impact of Nitrate Dose on Toluene Degradation under Denitrifying Condition - Kim, Dong-Ju; Park, Mee-Rye; Lim, Dae-Soon; Choi, Jae-Woo (HUMANA PRESS INC, 2013)
In this study, we investigated the impact of nitrate dose on toluene degradation by Pseudomonas putida to elucidate the upper limit of nitrate concentration and whether an optimum ratio of nitrate to toluene concentration exists. Batch microcosm studies were conducted in order to monitor toluene degradation for various ratios (2-20) of nitrate to toluene with nitrate concentrations ranging from 0 to 700 mg L-1 for a given toluene concentration of 50 and 25 mg L-1 during 4-day (short term) and 14-day (long term) incubation time, respectively. The short-term study revealed that nitrate concentration of 500 mg L-1 was toxic to bacteria and the optimum concentration was 300 mg L-1 yielding the highest toluene degradation rate (0.083 mg L-1 h(-1)). In the batch study of long term, toluene degradation was limited to 6 days after which the nitrate at 50 mg L-1 was depleted, indicating that nitrate was a necessary electron acceptor. For both batch studies, an optimum ratio of 6 was found yielding the highest toluene degradation rate. This indicates that an appropriate nitrate dose is essential for efficient degradation of toluene when bioremediation of groundwater contaminated with toluene is under consideration.